PENINGKATAN KETERAMPILAN LARI ESTAFET MATA PELAJARAN PENJASKES MATERI ATLETIK MELALUI MODEL EXPLICIT INSTRUCTION SISWA KELAS IV MINU SUMOKALI SIDOARJO - Muthoharoh, Rizqiyah (Journal Of Islamic Elementary School (JIES), 2017)
In the implementation of Physical Education and Health learning in class IV MINU Sumokali Sidoarjo showed that students’ relay running skills were in the low category, this was evidenced by the results of research interviews with fourth grade teachers, out of 21 students only 47.6% who completed the relay running skills. The reason is that relay running skills are taught without using special media or models. The teacher asks students to immediately practice according to their own imagination without any description from the teacher. The solution to overcome these problems is through the Explicit Instruction model. The objectives of this study are 1. To find out the application of the Explicit Instruction Model in learning to run the relay for fourth grade students at MINU Sumokali Sidoarjo. 2. To find out the improvement of relay running skills through the Explicit Instruction Model in Physical Education subjects for fourth grade students at MINU Sumokali Sidoarjo. The research method used in this research is Classroom Action Research using Kurt Lewin’s model which states that in one cycle consists of four main parts, namely planning, action, observation, and reflection. The research subjects were students of class IV MINU Sumokali Sidoarjo with a total of 21 students. The research was conducted in 3 cycles. The data collection techniques used were non-test (performance assessment) using the rubik for relay running skills assessment, observation using the teacher and student activity observation sheet instrument, interviews using an interview guide format and documentation. The results of the study can be explained that the application of relay running learning through the Explicit Instruction model during the implementation of physical education learning activities is very good. This can be seen from the acquisition of the final score of teacher activity of 77, while the acquisition of the final score of student activity of 65 then in cycle II from the acquisition of the final score of teacher activity of 85, while the acquisition of the final score of student activity was 78. After there was an improvement in cycle III the acquisition the final value of teacher activity is 88 and the acquisition of student activity scores is 83, it has increased. 2. The percentage of learning completeness of fourth grade students after the implementation of the Explicit Instruction model in the first cycle increased by 19.06% from 47.6% to 66.66%. The percentage of learning completeness in the second cycle increased by 19.34% from 66.66% to 86%. And the percentage of learning completeness in cycle III also increased by 23.74% from 86% to 90.4%. In cycle III, the percentage of students’ learning completeness in the very good category was declared to have met the performance indicators. The average in the first cycle is 69.5, the second cycle is 77.14 and the third cycle is 82.8.